Pattern and variation of the time budget of yellow-bellied marmots. Issue 3 (2nd July 2016) - Armitage, K.B.; Salsbury, C.M.
Abstract : We measured the time budgets of yellow-bellied marmots to determine what constraints limited energy acquisition and whether trade-offs occurred among the behaviors. Therefore, we focus on which behaviors form a consistent pattern among marmot populations, the degree of phenotypic plasticity in the time allocated to the behaviors, and the biotic and abiotic factors associated with variations in time allocations. Time budgets for 14 behaviors were recorded at six sites in the Upper East River Valley in western Colorado over two active seasons. Data were analyzed for cohort, day-period and season-period, and for interactions among the main effects. Sitting and vigilance, accounting for 63% of aboveground activity, are strongly associated with wariness, the need for marmots to monitor the presence of conspecific and predatory intruders. Foraging accounts for 15% of daily activity. These three activities are the major contributors to time budgets at all sites. Radiation, acting as a thermal constraint, greatly reduces activity during mid-day when radiation is intense. Sitting is the only major behavior to increase at mid-day, presumably to maintain wariness. Time allocations change little over the season-periods and foraging does not significantly increase in the weeks prior to hibernation. Young generally are less vigilant, often spend less time sitting and forage less than adults, but generally allocate more minutes to investigation. Time is a seasonal but not a daily constraint. Thermal constraints reduce overall daily activity, and digestive constraints limit foraging time. Sitting provides a reservoir of time that can be drawn upon when needed for other behaviors such that costly trade-offs are not evident. Time allocations for an activity may differ among sites; these differences and most significant differences, whether for cohort, day-period or season-period, are associated with the behaviors of a particular age/sex group, such as high time allocation to investigation by immigrant males.